Influence of different functionalized CdTe quantum dots on the accumulation of metals, developmental toxicity and respiration in different development stages of the zebrafish (Danio rerio) - Bosch, Suanne; Botha, Tarryn Lee; Wepener, Victor (Frontiers in Toxicology, 2023)
Introduction: The bioaccumulation and differential effects of cadmium tellurium quantum dot (CdTe QDs) nanomaterials with different functional groups are poorly understood in aquatic organisms. This study aimed to investigate the metal uptake, developmental effects, and respiratory effects of CdTe QDs with different functional groups (COOH, NH3, and PEG) on zebrafish embryos. Methods: Zebrafish embryos were exposed to carboxylate (COOH), ammonia (NH3), and polyethylene glycol (PEG) functionalized CdTe QDs at nominal concentrations of 0.5, 2, 4, 6, and 20 mg QDs/L. The materials were characterized in E3 exposure media and the metal uptake, developmental effects, and respiratory effects of zebrafish embryos were recorded. Results: The total Cd or Te concentrations in the larvae could not be explained by the metal concentrations or dissolution of the materials in the exposure media. The metal uptake in the larvae was not dose-dependent, except for the QD-PEG treatment. The QD-NH3 treatment caused respiration inhibition at the highest exposure concentration and hatching delays and severe malformations at low concentrations. The toxicities observed at low concentrations were attributed to particles crossing the pores in the chorion, and toxicities at higher concentrations were linked to the aggregation of particle agglomerates to the surface of the chorion impairing respiration. Developmental defects were recorded following exposure to all three functional groups, but the QD-NH3 group had the most severe response. The LC50 values for embryo development of QD-COOH and QD-PEG groups were higher than 20 mg/L, and the LC50 of the QD-NH3 group was 20 mg/L. Discussion: The results of this study suggest that CdTe QDs with different functional groups have differential effects on zebrafish embryos. The QD-NH3 treatment caused the most severe effects, including respiration inhibition and developmental defects. These findings provide valuable information for understanding the effects of CdTe QDs on aquatic organisms and highlight the need for further investigation.